2014
DOI: 10.4236/ajibm.2014.43018
|View full text |Cite
|
Sign up to set email alerts
|

Management Participation and Firm Performance

Abstract: This study sought to establish the relationship between management participation and firm performance. The study was premised in the applauded significant role that management participation plays on firm performance. However, a glaring knowledge gap established from literature review indicate a paucity of empirical support to the extent of the relationship with both the financial and none financial performance. Firms in Export Processing Zones (EPZs) in Kenya were studied. Significant relationship was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…Berbagai unsur atau elemen hasil kajian empiris terkait belum optimalnya pengelolaan keuangan desa menuju Good Village Governance (GVG), belum tersaji secara holistik dalam sebuah kajian empiris. Simpulan hasil kajian terkait pengelolaan keuangan entitas publik (Ely, 2009;Etienne, 2010;Otterlo, 2013;Namada et al,2014;dan Alemu, 2016) masih berfokus pada salah satu pilar dalam GG yaitu aparatur internal organisasi, sementara dua pilar GG lainnya belum tersaji secara komprehensif. Berbagai kajian empiris di atas juga masih didominasi pendekatan kuantitatif, yang merekomendasikan penggunaan pendekatan yang berbeda agar dapat dilakukan analisis lebih mendalam.…”
Section: Pendahuluanunclassified
“…Berbagai unsur atau elemen hasil kajian empiris terkait belum optimalnya pengelolaan keuangan desa menuju Good Village Governance (GVG), belum tersaji secara holistik dalam sebuah kajian empiris. Simpulan hasil kajian terkait pengelolaan keuangan entitas publik (Ely, 2009;Etienne, 2010;Otterlo, 2013;Namada et al,2014;dan Alemu, 2016) masih berfokus pada salah satu pilar dalam GG yaitu aparatur internal organisasi, sementara dua pilar GG lainnya belum tersaji secara komprehensif. Berbagai kajian empiris di atas juga masih didominasi pendekatan kuantitatif, yang merekomendasikan penggunaan pendekatan yang berbeda agar dapat dilakukan analisis lebih mendalam.…”
Section: Pendahuluanunclassified
“…Since no business scenario can assure economic stability, and the ability to control firm performance during a financial crisis becomes more difficult, a firm in difficulty must have the ability to recognize measures that allow it to respond effectively to new problems and adapt quickly to changes in the business environment (Gavrea et al, 2011). A number of studies focus on financial performance while other studies focus on non financial performance (Namada et al, 2014). According to Pandya and Rao (1998), management researchers have a preference for accounting variables as performance measures such as return on equity (ROE), return on investment (ROI), and return on assets (ROA).…”
Section: Firm Performancementioning
confidence: 99%
“…On the other hand, it was found that setting of goals and targets facilitate evaluation of firm performance (Arasa and K'Obonyo, 2012). Finally, in recent performance research, there has been a move from exclusive use of financial performance measures to insertion of non financial performance measures and this approach is considered practically valuable and in line with the multidimensionality of performance constructs (Namada et al, 2014).…”
Section: Firm Performancementioning
confidence: 99%
“…Even well-regarded celebrity CEOs seldom has totally untarnished reputations. The debate on celebrity CEO performance is inconclusive as a number of studies focus on financial aspects while others focus on non-financial performance [24].…”
Section: Introductionmentioning
confidence: 99%